Effects of Nonlinear Resistance Training with Curcumin Supplement on Liver Enzymes in Men with Non- Alcoholic Fatty Liver Disease - Baharak Moradi Kelardeh; Saeed Keshavarz; Mohammad Karimi (Islamic Azad University, 2017)
Introduction: Non-alcoholic fatty liver disease (NAFLD) has been recently very common; however, there is no definitive treatment for it. The present study aimed to investigate the effects of nonlinear resistance training with curcumin supplement on liver enzymes in men with non- alcoholic fatty liver disease. Methods: Forty-eight men with obesity and non-alcoholic fatty liver disease (mean age: 38.24 ± 6.59 years and BMI: 29.27 ± 4.43 kg.m-2) were selected and randomly divided into 4 groups including resistance training (RT), resistance training with curcumin supplement (RTCS), curcumin supplement (CS) and placebo (P). Before and after the protocol blood samples were taken to investigate the alanine aminotransferase (ALT), aspartate aminotransferase (AST) and Alkaline phosphatase (ALP) levels. One-way analysis of variance (ANOVA), paired sample t- test and Tukey post hoc test were used to analyze the data (p<0.05). Results: The results indicated significant difference between groups in ALT (p=0.0001) and AST (p=0.0001) levels following 12 weeks of exercise and supplement interventions. Post-hoc multiple comparison of ALT and AST was significant between RT and RTCS groups with CS and P groups (p=0.0001). ALP levels was not significantly different between groups (p=0.05). Conclusion: It seems that nonlinear resistance training with curcumin supplement improves the liver enzymes in men with non-alcoholic fatty liver disease.